A Comparative Investigation of the Rasch/Guttman Scenario Approach: Measuring Learning Motivation Toward Mathematics in Elementary School. (December 2022) - Leonid, Parmaksiz; Kanonire, Tatjana
The Rasch/Guttman scenario (RGS) measurement approach is a promising test development methodology. The purpose of this study is to compare the RGS measure of primary school students' motivation against more traditional self-report scales. The Scenario Scale of Extrinsic Motivation toward Math (SSEM-M) and its traditional counterpart were developed. The sample consisted of 1, 299 primary school students. Both measures demonstrated solid psychometric properties and sound evidence of validity. The comparative part of the research revealed notable differences in scores and factor structure. Scenario item composition appears to provide a slightly better motivation measurement than traditional composition. Further research considering response style and social desirability effects may be of interest.